Introducing clinical triage for oral surgery referral management in England. (3rd June 2014) - Coulthard, P.; Bailey, E.; Bridgman, C.M.
Abstract There has been a significant increase in the volume of referrals from general dentists to hospital oral surgery services over the last decade in England. The referral rate also varies between dentists and the referral systems need to become more sophisticated to understand demand and support needs led commissioning of services. Aim 1. Examine received referrals for hospital oral surgery and explore the reasons for selection to consultant led hospital‐based care or specialist primary care. 2. Determine the minimum data set required for the triager to make decisions for selection. Materials and methods Central capture and clinical triage of all referral letters received by the Oral Surgery department of a University Hospital. Results One thousand eight hundred and eighty‐five letters were triaged. Nineteen per cent were deflected to primary care including 2% for postgraduate training. Reasons for secondary care triage were anticipated surgical difficulty (43%), teaching and training (21%), need for general anaesthesia (16%), medical co‐morbidities (8%), other indicators (8%) and psychosocial (4%). Conclusions The introduction of a central triage system produced a significant amount of data and highlighted several important issues around decision‐making that need to be addressed for future development of the system. The study demonstrated that it is possible to direct a significant proportion of referrals to primary care that were destined for hospital consultant management. However, no account was taken of the quality of the care provided. Review of teaching and training systems in the future can and will be better informed by interrogation of intelligence from a more sophisticated and consistent needs assessment.